"It Didn't Seem Like Race Mattered": Exploring the Implications of Service-learning Pedagogy for Reproducing or Challenging Color-blind Racism. (July 2015) - Becker, Sarah; Paul, Crystal
Prior research measuring service-learning program successes reveals the approach can positively affect students' attitudes toward community service, can increase students' motivation to learn and ability to internalize class material, and can change their view of social issues. Studies also suggest that college students sometimes enter and leave a field site in ways that contribute to the reproduction of inequality. In this paper, we draw on three years of data from a service-learning project that involves sending college-age students (most of whom are white and materially privileged) into local, predominantly black, high-poverty neighborhoods to participate in community gardening. Using data generated by student assignments, we draw on service-learning research and critical race/whiteness scholarship to explore whether altering service-learning pedagogical tactics influences how students conceptualize and talk about race or if status factors, such as a student's own race, gender, and/or class, intersect to have greater impact on the racial logics they employ.